2018
DOI: 10.1038/s41393-018-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-management interventions for skin care in people with a spinal cord injury: part 1—a systematic review of intervention content and effectiveness

Abstract: Study designSystematic review.ObjectivesTo review the content and effectiveness of skin care self-management interventions for people with SCI.SettingInternational.MethodsWe searched electronic bibliographic databases, trial registers, and relevant reference lists. Eligibility criteria for the reviews of intervention content and effectiveness were identical with the exception of study design. The review of intervention content included non-randomized and randomized controlled trials (RCTs). The review of effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…One recent RCT [ 72 ] on health-related quality of life and satisfaction of patients with SCI and pressure injuries receiving real-time multidisciplinary videoconference consultations (video-telehealth) found videoconference-based care to be a safe and efficient way of managing pressure injuries, particularly for those individuals requiring long-term follow-up care and living far from the wound specialists. A total of 2 systematic reviews [ 55 , 56 ] and 1 scoping review [ 57 ] identified evidence to inform the development of telehealth techniques used to prevent, treat, and self-manage pressure ulcers in patients with SCI following discharge. One qualitative study that used semistructured interviews [ 34 ] and 1 modeled analysis [ 58 ] reported on patients’ experience using an educational mobile app for pressure ulcer prevention and evaluated costs and savings associated with telehealth services for preventing and treating pressure ulcers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One recent RCT [ 72 ] on health-related quality of life and satisfaction of patients with SCI and pressure injuries receiving real-time multidisciplinary videoconference consultations (video-telehealth) found videoconference-based care to be a safe and efficient way of managing pressure injuries, particularly for those individuals requiring long-term follow-up care and living far from the wound specialists. A total of 2 systematic reviews [ 55 , 56 ] and 1 scoping review [ 57 ] identified evidence to inform the development of telehealth techniques used to prevent, treat, and self-manage pressure ulcers in patients with SCI following discharge. One qualitative study that used semistructured interviews [ 34 ] and 1 modeled analysis [ 58 ] reported on patients’ experience using an educational mobile app for pressure ulcer prevention and evaluated costs and savings associated with telehealth services for preventing and treating pressure ulcers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The current literature points towards a new paradigm for treating and preventing PIs, including both pragmatic and health technology-based solutions, through the combination of different clinical approaches [59][60][61]. Despite the increase in clinical healthcare technology (CHT) innovation applied in PI prevention in recent years [62][63][64], solutions such as interface map pressure, telemedicine, and educational technologies (among others) have demonstrated moderate effectiveness in addressing a subset of risk factors [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…When a pressure injury develops, the responsibility should not be simply attributed to a lack of patient engagement [74]. It is important to acknowledge that not all pressure injuries can be prevented by behavioural measures [79,81,82], that the evidence in support of behavioural and educational interventions to prevent pressure injuries is mixed [83][84][85] and that the prevention of pressure injuries should be personalised and integrated into the complex self-management of the SCI [78,79,86,87]. This means, for instance, that HPs and health institutions must develop solutions that go beyond the personal partnership to better support patients who have different resources and attitudes toward self-management.…”
Section: Discussionmentioning
confidence: 99%